Biometric relationships of the pool barb puntius sophore (Hamilton 1822) (Cyprinidae) from three major rivers of Bangladesh - Hossain, Md. Yeamin; Rahman, Md. Mosaddequr; M. Abdallah, Elgorban; Ohtomi, Jun (Universiti Kebangsaan Malaysia, 2013)
The present study describes population structure (length-frequency distribution-LFD) and biometric relationships including length-weight relationship (LWR), length-length relationship (LLR), Fulton’s condition factor (K), relative weight (Wr) and form factor (a3.0) of Puntius sophore wild populations from three major rivers of different geographical locations of Bangladesh. A total of 784 specimens were caught by traditional fishing gear from March 2010 to February 2011. For each individual, the total length (TL), fork length (FL) and standard length (SL) were measured by digital slide calipers. Individual body weight (BW) was also taken by a digital balance. The results showed significant differences in TL-frequency distributions among populations (p<0.05), with larger mean TL size (6.92 ± 1.21 cm) was recorded from the Rupsha River. The coefficient b of the LWR was close to the isometric value (b≈3.000) in these rivers of Bangladesh, although it suggested negative allometric growth in the Padma River (b≈2.900). The results also indicated that the LWRs were highly correlated (r2>0.921). Fulton’s condition factor (K) showed significant variations (p<0.001) among the populations, with best performance by the Padma River, followed by the Jamuna and Rupsha River; whereas, relative weight (Wr) was close to 100 for all the populations, indicating the balance habitat with food availability relative to the presence of predators. The estimated values of a3.0 were as 0.0158, 0.0142 and 0.0152 for P. sophore in the Jamuna, Padma and Rupsha River. These results will be useful for fishery biologists and conservationists to suggest adequate regulations for sustainable fishery management and conservation its numerous stocks in the region.